SCIENTIFIC ILLUSTRATION IN THE REPRESENTATION OF PARASITIC ISOPODS - Mota Alves, André (2022)
Isopods are ectoparasitic crustaceans of marine and freshwater fish with diverse morphology where taxonomic studies involve a series of methods for collection, fixation and techniques for illustrating the species. These methods are applied in a series of studies involving ecology, distribution, biodiversity and morphology. However, approaches from the perspective of scientific illustration are often lacking in the study of parasitic isopods. This study provides a background on the illustration of these organisms by observing published works and presents the application of mixed color technique in the illustration of these invertebrates. This study combined information from the literature and ichthyoparasitological studies involving taxonomy and scientific illustration. The history of isopod illustrations revealed that some older illustrations present greater visual and scientific elaboration compared to some recent ones, despite presenting greater taxonomic and visually less attractive elements, such as the application of pointillism and finishing of the isopod body, demonstrating that it is crucial to combine scientific knowledge and mastery of the illustrative technique. The illustrations of isopods demonstrate the effectiveness of mixed techniques, allowing overlapping of materials, didactics in the rigorous taxonomic view, highlighting the color preserving morphological aspects, in addition to rescuing a similarity to the first descriptions in colors from 1800-1900. This work is the first to describe a history of scientific representations of parasitic isopods over time and to present the mixed technique as a possibility of scientific illustration for this taxonomic group.